Miejsce i rola reformującej się edukacji w procesie transformacji ustrojowej społeczności lokalnych Pomorza - w świetle badań empirycznych = Position and role of education under reform in the transformation process of Pomeranian local communities (based on empirical research) - Gazicki, Andrzej; Socha, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the region of Western and Mid Pomerania evaluations and opinions concerning the matter of the availability of secondary schools close to where people live seem to be very similar. The arrangement of these opinions, however, is definitely different. The biggest city agglomerations are clearly privileged, which for certain reasons is understandable.
Keywords: transformacja ustrojowa; edukacja; Polska - 20 - 21 w.